Model Pembelajaran Menulis Deskripsi Berbasis Literasi Digital dan Kearifan Lokal di Sekolah Menengah Pertama: Sebuah Studi Kualitatif - Ilawati Ilawati; Eko Suroso (Pusat riset dan Inovasi Nasional, 2025)
This study aims to examine the effectiveness of implementing a descriptive writing learning model based on digital literacy and local wisdom in improving writing skills, learning motivation, and cultural character among junior high school students. Employing a descriptive qualitative approach with a case study design, the research was conducted at SMP Negeri 2 Kroya, Cilacap Regency, during the 2025–2026 academic year. Data were collected through participatory observation, in-depth interviews, and document analysis, and were subsequently analyzed using the interactive model developed by Miles, Huberman, and Saldaña. The findings indicate that the application of this model effectively enhances students’ writing abilities in terms of content, structure, language style, and digital literacy ethics. The integration of digital technology fosters the development of cognitive, technical, and social literacy, while the reinforcement of local wisdom cultivates cultural awareness, regional identity pride, and reflective thinking skills. Writing activities evolved into collaborative and creative processes that combine cultural exploration with the ethical use of digital technology. From a pedagogical perspective, this model aligns with the principles of deep learning promoted by the Kurikulum Merdeka and contributes to strengthening the Eight Dimensions of Graduate Competencies, particularly in critical reasoning and problem-solving, creativity and innovation, collaboration and mutual cooperation, as well as the development of the Pancasila student profile and global citizenship. Therefore, the descriptive writing learning model based on digital literacy and local wisdom can be regarded as an innovative strategy in Indonesian language education to realize a contextual, reflective, creative, and culturally grounded learning process.